Physicochemical and microbiological evaluation of corrientes artisanal cheese during ripening - Vasek, Olga M. (2013)
The aim of this study was to evaluate some physical and chemical parameters (total solids, pH, acidity, fat, acid degree value of fat, salt, protein and nitrogen fractions) and their effects on the beneficial (lactic acid bacteria: LAB) and undesirable microbial populations (coliforms, Escherichia coli, Staphylococcus aureus, moulds, and yeast) during ripening of Artisanal Corrientes Cheese, an Argentinian cow's milk variety, to determine whether a longer ripening period than usual improve its hygienic-sanitary quality. The protein content was much higher than that of other cow's milk cheeses with similar values of fat. The larger peptides showed values three times higher in the 30 day-old cheese than those obtained in the beginning of the process. Staphylococcus aureus and Escherichia coli were detected (3.04 ± 1.48 log10 cfu/g of cheese, 2.21 ± 0.84 log10 MPN/g of cheese) even at 15 and 30 days of ripening, respectively. The distribution of three hundred LAB strains classified to the genus level (lactococci:lactobacilli:leuconostocs) was maintained during the ripening period. The high number of LAB in rennet may have contributed to the fermentation as a natural whey starter, unknown source of LAB for this specific cheese so far. The physicochemical changes that occur during ripening were not big enough to inhibit the growth of undesirable microorganisms.